Incidence and survival in oral and pharyngeal cancers in Finland and Sweden through half century - Koskinen, Anni I; Hemminki, Otto; Försti, Asta; Hemminki, Kari (BMC cancer, 2022)
BACKGROUND: Cancers of the oral cavity and pharynx encompass a heterogeneous group of cancers for which known risk factors include smoking, alcohol consumption and human papilloma virus (HPV) infection but their influence is site-specific with HPV mainly influencing oropharyngeal cancer. Their incidence and survival rates are not well known over extended periods of time. PATIENTS/METHODS: Data were obtained for Finnish (FI) and Swedish (SE) patients from the Nordcan database recently updated through 2019. Age-adjusted incidence trends (FI from 1953, SE from 1960) and relative survival rates for years 1970 through 2019 were calculated. RESULTS: We observed a prominent increase in oral and oropharyngeal cancers in FI and SE men and women but the trend for oral cancer was interrupted for SE men in 1985 and possibly also for FI and SE women in 2015. The trend changes in male and female oral cancer was confirmed in data for Denmark and Norway. Relative survival for these cancers has improved overall but they differed for one cluster of oral, oropharyngeal and nasopharyngeal cancers with 60-70% 5-year survival in the last period and hypopharyngeal cancer with 25% male survival. In all these cancers, survival for old patients was unfavorable. DISCUSSION/CONCLUSION: We hypothesize that reduction in smoking prevalence helped to stop the increase in oral cancer especially in men. As the prevalence of smoking is decreasing, HPV is becoming a dominant risk factor, particularly for the increasing oropharyngeal cancer. Prevention needs to emphasize sexual hygiene and HPV vaccination.
Keywords: nádory hltanu; Mouth Neoplasms; Male; Middle Aged; Risk Factors; infekce papilomavirem; Papillomavirus Infections; Aged; Alcohol; mužské pohlaví; senioři; incidence; registrace; nádory orofaryngu; Oral cancer; Smoking; Pharyngeal Neoplasms; lidé; ženské pohlaví; Human papilloma virus; Humans; Oropharyngeal Neoplasms; Pharyngeal cancer; Sweden; rizikové faktory; pití alkoholu; Alcohol Drinking; Finsko; Registries; Female; nádory úst; lidé středního věku; Incidence; Finland; kouření; Švédsko